Terrorist profiling and law enforcement : detection, prevention, deterrence - McGuirk, Noel (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This book analyses the usefulness of terrorist profiling utilised by law enforcement officers as a pre-emptive means to assist them in the detection, prevention and deterrence of terrorism and/or its preparatory activities. It explores two main themes arising from the phenomenon of terrorist profiling; the lawfulness of terrorist profiling and the utility of profiling. These two themes are explored in three separate parts. First, the book begins by drawing upon human rights concerns arising from the use of terrorist profiling by law enforcement officers. Second, is the presentation of an analytical framework capable of making determinations on the usefulness of terrorist profiling. This framework develops a profiling spectrum that ranges from formal and informal manifestations of terrorist profiling that forms the basis for evaluating its usefulness. Finally, the work presents an examination of various manifestations of terrorist profiling by separating the analysis of the "construction" of profiles on the one hand, from their "application", on the other, so as to be able to identify and examine profiling's usefulness as a technique to assist law enforcement officers make predictions about likely offender characteristics"--
OCLC-licensed vendor bibliographic record.
Keywords: Terrorism -- Prevention; Criminal behavior, Prediction of; Law enforcement; LAW / General; LAW / Civil Rights; LAW / Constitutional